Step-by-step Solution

Solve the equation $11x+5x-1=65x-36$

Go!
1
2
3
4
5
6
7
8
9
0
a
b
c
d
f
g
m
n
u
v
w
x
y
z
.
(◻)
+
-
×
◻/◻
/
÷
2

e
π
ln
log
log
lim
d/dx
Dx
|◻|
=
>
<
>=
<=
sin
cos
tan
cot
sec
csc

asin
acos
atan
acot
asec
acsc

sinh
cosh
tanh
coth
sech
csch

asinh
acosh
atanh
acoth
asech
acsch

Step-by-step Solution

Problem to solve:

$11x+5x-1=65x-36$

Learn how to solve equations problems step by step online.

$16x-1=65x-36$

Unlock this full step-by-step solution!

Learn how to solve equations problems step by step online. Solve the equation 11x+5x-1=65x-36. Combining like terms 11x and 5x. We need to isolate the dependent variable x, we can do that by subtracting -1 from both sides of the equation. Divide both sides of the equation by 16. Split the fraction \frac{-35+65x}{16} in two fractions with common denominator 16.

Final Answer

$x=\frac{5}{7}$
$11x+5x-1=65x-36$

Main topic:

Equations

Time to solve it:

~ 0.07 s